A Generational Cohort Comparison of Endurance Sport Participant Involvement - Jason A. Rice (Journal of Applied Sports Management, 2015)
While traditional team sport participation numbers are unstable, trends indicate individual endurance event participation is moving in the opposite direction. Simultaneously, Generation Y, North America's largest teen population in history, is entering its wealth accumulation stage. In an effort to understand more about this group and their potential influence on such trends, the purpose of the current study was to investigate involvement of endurance event participants within the Generation Y cohort and a comparison group of older generational cohorts. This research has applied an approach, whereby use of quantitative methods was utilized for sample selection and description, while qualitative methods were predominantly used to analyze the research questions. A cross-group comparative analysis was conducted with six Generation Y members and six non-Generation Y members across differing levels of involvement. While most study participants held comparable social influences along with achievement based motivations for participation, differences were present in the range of motivations present and obstacles encountered. Marketers may use promotions to leverage the post event euphoria experienced by participants to advocate their friends to join future events. Additionally, capitalizing on achievement motivations would be most effective in targeting Generation Y members.
Keywords: sport involvement; generational cohort; participant sport; endurance sport